Improving of proton therapy of breast cancer via AuNPs injection - Hsseinimotlagh, S.N.; Shakeri, A. (Recent Contributions to Physics, 2025)
Beam therapy plays an important role in the treatment of cancer, which is the most common and successful form of treatment used after surgery. In proton therapy, proton beam (PB) particles irradiate the tumor. To enhance the treatment of breast tumor, it is possible to inject gold nanoparticles (AuNPs) into the tumor at the same time as irradiating the PB. The aim of this paper is simulation of breast tumors treatment using PBs and injecting AuNPs with different concentrations, simultaneously. Therefore, we introduce the breast phantom (BP), then irradiate it with a proton pencil beam which is also injected with AuNPs at the same time. To show the enhancement of the absorbed dose in the tumor, we use the MCNPX.2.6 code. Findings of our simulations show that the location of the Bragg's peak within the tumor shifts to higher depths with increasing energy. Also, by injecting AuNPs in different amounts of 10, 25, 50 and 75mg/ml with PB irradiation simultaneously, the rate of absorbed dose increases up to 1.75% compared to the non-injected state. Our results also show that optimal range of proton energy that creates Bragg peaks within the tumor is 52 up to 65 MeV, which causes the creation of spread out of Bragg peak. It should be noted that the amount of absorbed dose is affected by quantities such as total stopping power, average Coulomb scattering angle, CSDA and straggling range. This work offers new insights based on the use of AuNPs in the treatment of breast cancer through proton therapy and indicates that the addition of AuNPs is a promising strategy to increase the killing of cancer cells while irradiating fast PBs. In fact, the results of this study confirm the ability of AuNPs to enhance treatment by increasing the absorbed dose in breast tumors using proton therapy